2022
DOI: 10.1530/eor-22-0031
|View full text |Cite
|
Sign up to set email alerts
|

Management of fracture-related infection in low resource settings: how applicable are the current consensus guidelines?

Abstract: The global burden of fracture-related infection (FRI) is likely to be found in countries with limited healthcare resources and strategies are needed to ensure the best available practice is context appropriate. This study has two main aims: (i) to assess the applicability of recently published expert guidance from the FRI consensus groups on the diagnosis and management of FRI to low- and middle-income countries (LMICs); (ii) to summarise the available evidence on FRI, with consideration for strategies applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…Several studies analysed the bacteriological profile in long bone osteomyelitis [3,[5][6][7][8][12][13][14][15][16]. Reports from low resources settings and developing countries are sparse [4,9,10,17,18]. Nevertheless, other studies investigated the aetiology and bacteriology of COM in a diabetic foot or joint replacement infection or mixed group of patients [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies analysed the bacteriological profile in long bone osteomyelitis [3,[5][6][7][8][12][13][14][15][16]. Reports from low resources settings and developing countries are sparse [4,9,10,17,18]. Nevertheless, other studies investigated the aetiology and bacteriology of COM in a diabetic foot or joint replacement infection or mixed group of patients [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to raise voices about the differences in causes and bacteriological profiles of COM in low resources settings. The management of chronic osteomyelitis in low resources countries had more obstacles compared to the developed world [10]. However, the high-quality literature about the bacteriological spectrum and sensitivities profile was driven by developed countries [12,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McNally et al reported 96% eradication of infection in 76 infected tibial non-union cases treated by Ilizarov treatment protocols and either primary skin closure or flap cover during the index surgical procedure [ 30 ]. Others have similarly reported success rates of over 90% in patients suffering from chronic osteomyelitis managed with debridement and primary soft tissue closure at the same time [ 31 , 32 ].…”
Section: Timing Of Soft Tissue Closurementioning
confidence: 99%
“…However, a major complication in surgery is postoperative fracture-related infection, which may lead to nail failure, revision surgeries, nail removal and, in severe cases, amputation or death [ 3 ]. There is limited information available on fracture-related infections in resource-limited settings, and a 2022 review noted that 78.5−100% of authors on fracture-related infection consensus guidelines were from high-income countries [ 4 ]. Nevertheless, a large, international prospective study using an international online database called the “Surgical Implant Generation Network” (SIGN) found that 11.9% of patients with IM nail-treated open tibial fractures treated in low- and middle-income countries developed fracture-related infections [ 5 ].…”
Section: Introductionmentioning
confidence: 99%